Beliefs, behaviour, and blood pressure: preliminary analysis from a pharmacy-based hypertension visualisation intervention to support medication adherence. (30th November 2022) - Brown, S; McDonnell, B; McRae, D; Hallingberg, B; Angel, P; Khan, I; James, D H
Abstract: Introduction: Hypertension is the leading preventable risk factor for cardiovascular disease, with an estimated prevalence of 31% worldwide 1 . Antihypertensive medication reduces both blood pressure (BP) and cardiovascular risk; however, approximately 50% of patients become nonadherent to antihypertensives within a year of treatment initiation 2 . Nonadherence can be considered as either intentional or unintentional. Research suggests that rather than being a solely passive process, illness beliefs and treatment perceptions may influence nonintentional nonadherence 3, highlighting the importance of considering patients' beliefs when supporting adherence. The use of visuals is one method to aid understanding of complex health information and influence treatment beliefs. Aim: To investigate the feasibility and acceptability of a community pharmacy-based visualisation intervention (ViSTA-BP) and explore the preliminary effect on patients' perceptions of hypertension, medication adherence and blood pressure. Methods: ViSTA-BP is a digital intervention that allows users, through real-time animations, to visualise both the condition that is hypertension and how blood pressure affects the circulatory system. The purpose of ViSTA-BP was to improve patients' understanding of hypertension, increase perceived necessity of treatment and ultimately support medication adherence. A mixed-methods pre-post design pilot study was conducted. NHS Research Ethics Committee Wales Rec 5 (reference 20/WA/0280) and Cardiff Metropolitan University (reference PGR-3806) granted ethical approval. The intervention was consultation-based and researcher-facilitated. Outcomes were recorded at baseline, immediately post-intervention, and at three-months. Validated questionnaires were used to measure illness and treatment beliefs (Brief Illness Perception Questionnaire (B-IPQ)/Beliefs about Medicines Questionnaire (BMQ)), adherence captured using self-report measures (Medicines Adherence Rating Scale (MARS-5)/recent adherence questionnaire) and medication dispensing/collection data. BP was measured at baseline and 3-month follow-up. Semi-structured interviews with patients and pharmacists explored intervention acceptability. Results: Pharmacists recruited 69 patients with hypertension across five community pharmacies (CP) in South Wales; 54 attended the three-month follow-up. The ease of participant recruitment and high retention rates demonstrated the feasibility of delivering ViSTA-BP in this setting. ViSTA-BP content and the CP location were acceptable to patients and pharmacists. Time to deliver the intervention was a concern for pharmacists but not patients. There was no statistically significant change in adherence outcomes at three-month follow-up; however, the median scores for both self-report questionnaires were maximal at baseline. Changes were seen in illness belief scores, with a significant improvement in total B-IPQ score over time (p=0.04). Significant changes in B-IPQ treatment control (p=0.01), illness coherence (p<0.001) and BMQ Necessity subscale scores (p=0.003) were reported at all time-points. There was a statistically significant improvement in both systolic (SBP) (p<0.01) and diastolic BP (DBP) (p=0.03) three-months post-intervention. At baseline, 31% of participants had SBP at or below the UK target; however, at three-month follow-up, 59% were at or below the UK target. Discussion/Conclusion: ViSTA-BP was considered a feasible researcher-facilitated intervention in this CP setting. Improvements seen in blood pressure control, patients' understanding of hypertension, and perceptions of utility and necessity of treatment highlight the potential for the ViSTA-BP intervention to help reduce cardiovascular risk in the future. While preliminary analysis shows promise, further adequately powered research studies are necessary to evaluate future ViSTA-BP impact. References: 1. Mills KT, Stefanescu A, He J. The global epidemiology of hypertension. Nat Rev Nephrol . 2020;16(4):223-237. doi:10.1038/s41581-019-0244-2 2. Vrijens B, Antoniou S, Burnier M, de la Sierra A, Volpe M. Current situation of medication adherence in hypertension. Front Pharmacol . 2017;8. doi:10.3389/fphar.2017.00100 3. Gadkari AS, McHorney CA. Unintentional non-adherence to chronic prescription medications: how unintentional is it really? BMC Health Serv Res . 2012;12(1):98. doi:10.1186/1472-6963-12-98